MEKANISME PERTAHANAN DIRI TOKOH PEREMPUAN DALAM NOVELET RYOUJUU KARYA YASUSHI INOUE - Yuliari, Gusti Ayu Putu (Humanis, 2015)
This research entitled "Self Defense Mechanism of Female Characters in the novella Ryoujuu written by Yasushi Inoue”. The aims of this research are to find out the conflicts and self defense mechanism of female characters in the novella, and to increase the appreciation towards Japanese literature in society. This research used a descriptive method of analysis and informal method. The theories used in this research are conflict theory by Wellek and Warren supported by Stanton and Jones’s conflict theory. The second theory is self defense mechanism theory by Sigmund Freud. The result shows that the internal conflict and social conflict happened to female characters Midori, Saiko, and Shoko has brought self defense mechanism into them. The substances of self defense mechanism used by female characters in this novella are reaction formation, regression, displacement, aggression, apathy, repression and rationalization. Lastly, the failure of self defense mechanism was found in Saiko character that made her committed suicide.
Keywords: Conflict, Self Defense Mechanism , Female Character